2015
DOI: 10.3168/jds.2014-8662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying dietary ratios of corn silage to alfalfa silage on digestion of neutral detergent fiber in lactating dairy cows

Abstract: An in vivo study was performed to test an in vitro procedure and model that predicts total-tract neutral detergent fiber (NDF) digestibility for lactating dairy cattle. Corn silage (CS) and alfalfa silage (AS) were used as forages for this study. These forages had similar NDF composition, but fiber in the CS contained less indigestible NDF compared with AS (35.5 and 47.8% of indigestible NDF, respectively). The in vitro method estimated rate of digestion of alfalfa potentially digestible NDF to be approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
5
13
0
2
Order By: Relevance
“…The nutrient contents of the silage used in this research are given in Table 1. The results of the present study were similar to those of many studies in terms of CP (19)(20)(21), ADL (19,21,22), ash (21,23,24), EE (25), NDF (19,21), and ADF (19,21,23). The mean cumulative gas production of 100-ppm, 200-ppm, and 300-ppm concentrations from each cuminaldehyde, eugenol, and thymol addition to alfalfa silage at 2, 4, 8, 16, 24, 48, 72, and 96 h incubation were significantly lower than those of the control group (P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The nutrient contents of the silage used in this research are given in Table 1. The results of the present study were similar to those of many studies in terms of CP (19)(20)(21), ADL (19,21,22), ash (21,23,24), EE (25), NDF (19,21), and ADF (19,21,23). The mean cumulative gas production of 100-ppm, 200-ppm, and 300-ppm concentrations from each cuminaldehyde, eugenol, and thymol addition to alfalfa silage at 2, 4, 8, 16, 24, 48, 72, and 96 h incubation were significantly lower than those of the control group (P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The lowest postruminal digestibility of ruminal-undegraded protein in silage prepared with urea may have resulted from the greater protein degradability in rumen [46]. Post-ruminal NDF disappearance was similar for three silages than their untreated controls and was approximately 5-9% in the intestine which is fairly similar with the study of Lopes et al [52] and estimation of Cornell Net Carbohydrate and Protein System Model [53] which reported that hindgut digestion of NDF is assumed to be 10% of total NDF digestion. Throughout the present study, total tract protein disappearance was not significantly affected by the silage additives (P>0.05).…”
Section: Ruminal and Post-ruminally Digestibilitysupporting
confidence: 78%
“…Moreover, Faciola and Broderick (2014) observed NDF and ADF digestibilities of 44 and 49%, respectively, when cows were fed the control diet (i.e., with no added lipid) with a 10:50 ratio of corn silage: alfalfa silage DM. Although Lopes et al (2015) found greater indigestible NDF in alfalfa silage versus corn silage, apparent total-tract NDF digestibility increased as the dietary proportion of alfalfa silage increased. This result was explained by a rate of ruminal digestion of digestible NDF in alfalfa silage that was twice as rapid as that for corn silage.…”
Section: Nutrient Digestibility and N Excretionmentioning
confidence: 70%